All Questions Topic List
Integration Questions
Previous in All Question Next in All Question
Previous in Integration Next in Integration
Question Number 168762 by Dildora last updated on 17/Apr/22
Commented by cortano1 last updated on 17/Apr/22
∫2sin12xcos12x2cos12x(cos12x+sin12x)dx=∫sin12xcos12x+sin12xdx=∫2sinucosu+sinudu;[12x=u]2sinucosu+sinu=A(sinu+cosusinu+cosu)+B(d(sinu+cosu)sinu+cosu)⇒2sinu=Asinu+Acosu+Bcosu−Bsinu⇒2sinu=(A−B)sinu+(A+B)cosu{A−B=2A+B=0⇒{A=1B=−1I=∫0π42sinusinu+cosudu=∫0π4du−∫0π4d(sinu+cosu)sinu+cosu=π4−[ln∣sinu+cosu∣]0π4=π4−ln2
Commented by Dildora last updated on 17/Apr/22
thankyou
Terms of Service
Privacy Policy
Contact: info@tinkutara.com